Наконечники ремней из могильника Нейзац - Храпунов, И.Н. (Материалы по археологии, истории и этнографии Таврии, 2008)
Могильник Нейзац расположен в 20 км к востоку от Симферополя, в самом центре крымских предгорий, в долине реки Зуя. Он использовался во II- IV вв. н. э. В 1996, 1997, 1999-2007 гг. на территории могильника раскопано 352 погребальных сооружения, в том числе склепы, подбойные и грунтовые могилы. Многие из них содержали многократные погребения. В качестве погребального инвентаря использовалось значительное количество разнообразных вещей. Среди них оказались 77 наконечников ремней, которые публикуются в данной статье. The cemetery of Neizats is situated at the distance of 20 kms to the east from Simferopol, in the very centre of the Crimean foothills, in the valley of the Zuja River. It functioned in the 2nd - 4th century AD. A large number of different things were used as funeral equipment; among them there were 77 strap-ends which are published in this article. General information about them is represented in the table. Strap-ends are divided into eleven types; the types are, in their turn, subdivided into variants. Judging by their location in graves and their combination with other finds the strap-ends were used as details of clothes, footwear and ammunition of people as well as elements of horse harness. The correlation of forms and ornamentation of strap-ends with their function has not been established yet.